Physicochemical and quality characteristics of pili (Canarium ovatum) nut oil obtained from mechanical press extraction - Aemelda Nastiyana Anak Adin; Angela Anak Gawai; Ivy Christy Josli; Lydia Nakolas; Aisyah Amini Amin; Jain Linton; Nur Hanisah Azmi; Fan, Hui Yin; Syariena Arshad; Bangun Prajanto Nusantoro; Helmi Wasoh; Yanty Noorzianna Abdul Manaf (UniSE Press, 2024)
Pili (Canarium ovatum) nut oil from Sabah, Malaysia was extracted using mechanical press extractor. The purpose of this study was to investigate the characteristics of pili nut oil in terms of physicochemical and quality properties. The yellowish oil had about 40% of oil content. The slip melting point and iodine value of the extracted pili nut oil were 19.5 °C and 96.75 g I2/100 g, respectively. The major fatty acids found in the oil were oleic and palmitic acids. The major triacylglycerols were POO (28.01%) and PPO (20.58%). The extracted oil was found to be of good quality and had low peroxide content (2.56 meq/kg oil) and p-anisidine values (0.14 meq O2/kg).